A comparison of pectoral fin ray morphology and its impact on fin ray flexural stiffness in labriform swimmers. (25th April 2018) - Aiello, Brett R.; Hardy, Adam R.; Cherian, Chery; Olsen, Aaron M.; Orsbon, Courtney P.; Hale, Melina E.; Westneat, Mark W.
Abstract: The organization of tissues in appendages often affects their mechanical properties and function. In the fish family Labridae, swimming behavior is associated with pectoral fin flexural stiffness and morphology, where fins range on a continuum from stiff to relatively flexible fins. Across this diversity, pectoral fin flexural stiffness decreases exponentially along the length of any given fin ray, and ray stiffness decreases along the chord of the fin from the leading to trailing edge. In this study, we examine the morphological properties of fin rays, including the effective modulus in bending ( E ), second moment of area ( I ), segmentation, and branching patterns, and their impact on fin ray stiffness. We quantify intrinsic pectoral fin ray stiffness in similarly sized fins of two closely related species that employ fins of divergent mechanics, the flapping Gomphosus varius and the rowing Halichoeres bivittatus . While segmentation patterns and E were similar between species, measurements of I and the number of fin ray branch nodes were greater in G. varius than in H. bivittatus . A multiple regression model found that of these variables, I was always significantly correlated with fin ray flexural stiffness and that variation in I always explained the majority of the variation in flexural stiffness. Thus, while most of the morphological variables quantified in this study correlate with fin ray flexural stiffness, second moment of area is the greatest factor contributing to variation in flexural stiffness. Further, interspecific variation in fin ray branching pattern could be used as a means of tuning the effective stiffness of the fin webbing to differences in swimming behavior and hydrodynamics. The comparison of these results to other systems begins to unveil fundamental morphological features of biological beams and yields insight into the role of mechanical properties in fin deformation for aquatic locomotion. Abstract : This study quantifies pectoral fin ray morphology and its relationship to stiffness. Variation in fin ray second moment of area explains the majority of the variation in stiffness, providing insight into the relationship between form and function.